Exposure to paediatric end-of-life care: the experiences and coping strategies of paediatric registrars in South Africa - Sullivan, Audrey Louise (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.